Dapsone-induced methemoglobinemia in a patient of lichen planus: A case report - Kanisha Shah; Sapna Gupta; Pooja Agarwal; Supriya Malhotra (Apollo Medicine)
Introduction: Methemoglobin (MetHb) is the rare form of hemoglobin (Hb) produced by abnormal oxidation of Hb. Methemoglobinemia may be hereditary or acquired after exposure to certain drugs, toxins, chemicals, food, etc., Case Presentation: Here, we report a case of methemoglobinemia induced by dapsone in a young girl who presented with respiratory distress and was treated successfully with methylene blue (MB). Conclusion: MetHb levels can be seen increased inpatient on dapsone. Methemoglobinemia is a rare cause of respiratory distress and tachypnea in a patient on dapsone. MB and Vitamin C are recommended treatments in such cases.